Transforming Traditional Preaching Through Digital Marketing for More Effective Islamic Education - Moh. Kamil; Rifka Jannatul Firdausiyah; Muhammad Durrin Ni’am; Moh. Rofik; Ittaqillah Haistuma Kunta; Siti Nur Aviatun (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine how transforming traditional da'wah through the use of digital marketing can increase the effectiveness of Islamic education, both in terms of disseminating knowledge and reaching a wider audience. The method used in this study is a qualitative approach with literature review and in-depth interviews. Data was collected through relevant sources such as scientific articles, books, and discussions with digital da'wah practitioners and Islamic educators. The results show that integrating traditional da'wah with digital marketing can expand access to Islamic education, accelerate the dissemination of information, and enhance interaction with audiences. The use of digital platforms such as social media, blogs, and podcasts can attract the interest of the younger generation to become more actively involved in da'wah activities and Islamic education. The implication of this study is that traditional da'wah needs to adapt to technological developments to increase its effectiveness. The use of digital marketing in the context of Islamic education opens new opportunities for broader dissemination of knowledge and creates innovative ways for Muslims to learn and interact with da'wah.